SIKAP MASYARAKAT KOTA DENPASAR TERHADAP INFORMASI BOHONG DI FACEBOOK - Juniantari, Ni Ketut; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT The development of uncontrolled mass media leads to information lying or hoax. There are a total of 800 thousand hoax spreading sites in Indonesia that were revealed in the year 2017. Hoax cause dangers that can cause panic in the public. Facebook becomes an informational channel that contains the highest hoax content in the new media.  The high phenomenon of this hoax caused the curiosity of researchers to measure the attitude of the people of Denpasar to Hoax on Facebook. According to Azwar, attitudes can be measured by distinguishing three components, namely cognitive, affective, and conative. This research uses a descriptive quantitative method. Technical sampling is stratified proportional. The analytical techniques used are statistic descriptive. Results showed that on the cognitive components, the community of Denpasar has excellent in addressing hoax on Facebook. However, it has enough affective of curiosity and is quite a contemplative in addressing Hoax on Facebook. Keywords: Attitude, Denpasar, Facebook, Hoax